THE IMPACT OF PROMOTIONS AND TESTIMONIALS ON PURCHASING ALUNICORN PRODUCTS AS MEDIATED BY TRUST - Zarkasi Zarkasi (BADAN PENERBIT STIEPARI PRESS, 2023)
This study aims to determine the influence of promotions and testimonials on purchase intention and trust as mediating variables. This research method uses a quantitative approach by distributing questionnaires to 97 consumers. This study gives the result that promotion has a significant effect on purchase intention through the mediating variable of trust and testimonials does not affect purchase intention.